La religiosità popolare in Val Canale Il teschio lavato e avvolto nel panno - Gliha Komac, Nataša (Studia Mythologica Slavica Supplementa, 2015)
The monograph La religiosità popolare in Val Canale: Il teschio lavato e avvolto nel panno (Popular piety in the Canale Valley: The skull that is washed and wrapped in cloth) is re-writed and updated version of Slovenian monograph Ljudska religioznost v Kanalski dolini: O umiti in v prt zaviti lobanji (2014). The book illustrates the festive year of Slovenes in the Canale Valley from the perspective of current ritualistic practices (still in use today). The identifying elements of the Slovenian linguistic community are recognizable in the implementation of various (popular) religious practices by the local population. The author presents the rituals (with selected prayer formulas), described as an integral part of their life by Slovenian-speaking informants - all of whom are indigenous, native people of the Canale Valley - that was described, from the point of view of experts in the fields (e.g. Kuret 1989) as typical of the Slovenian community in general.